Kajian Rantai Pasok Buah Kelapa Di Bengkulu - Diah Azhari; Ade Apriado; Andwini Prasetya; Methatias Ayu Moulina (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Coconut is a plantation crop that contributes quite a lot to the Indonesian economy. The largest supply of coconuts in the city of Bengkulu comes from Seluma and North Bengkulu. This study aims to analyze the supply chain management of coconuts in Bengkulu City. It begins with the initial exploration stage of the coconut supply chain. The primary and secondary data obtained were analyzed by descriptive tabulation and simple statistics, added value analysis used was added marketing value. The results showed that the primary members of the coconut supply chain in Bengkulu City were inter-regional traders, wholesalers, retailers, household consumers and home industries. The supply chain flow pattern in Bengkulu City is 3 patterns. Added value analysis conducted by retailers can provide greater added value of Rp. 1000 compared to other supply chain members with a percentage of 100%. Meanwhile, wholesalers and inter-regional traders, after deducting labor, namely Dewa market of Rp. 996.30 with a percentage of 89.97%, Sunday market of Rp. 766.67 with a percentage of 65.71%, Panorama market is Rp. 956.90 with an added value percentage of 82.22%, Seluma of Rp. 764.71 with a percentage of 776.47% and North Bengkulu of Rp. 700 with a percentage of 87.5%.